Analisis Perbandingan Kualitas Data Rekam Medis Manual dan Elektronik di Rumah Sakit Panti Waluyo Yakkum Surakarta - Nurfika Nurfika; Sri Wulandari; Dwi Iskandar (MEDIKA TRADA, 2026)
The quality of medical record data is an important component in supporting the quality of health services, decision making, and continuity of patient services. This study aims to compare the quality of manual and electronic medical record data based on the completeness of the discharge summary at Panti Waluyo Yakkum Hospital, Surakarta. The research method used a comparative quantitative design with a cross-sectional approach on 756 samples, consisting of 378 manual medical records and 378 electronic medical records, with descriptive analysis and the Mann Whitney test. The results showed the completeness level of manual medical records was 64.08%, while the electronic medical records were 98.94%. The Mann Whitney test showed a significance value of 0.000 (p<0.05) with a manual Mean Rank of 217.50 and electronic 539.50, so there was a significant difference between the two. Electronic medical records showed better data quality because the system was more structured and integrated. In conclusion, the data quality of electronic medical records was better than manual medical records. Hospitals are advised to optimize the use of electronic medical records, evaluate the completeness of documents, and improve the training of health workers.